PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DISERTAI LDS UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII DI SMPN 9 PADANG TAHUN PELAJARAN 2012/2013 - Naini, Iis; Indriati, Gustina; Sari, Liza Yulia (STKIP PGRI Sumbar, 2013)
ABSTRACT This researchs motivated by the lack results of biological studies due to several factors , including the lack of communication with the student teacher and student fellow students in the learning process , activity and motivation of students in the learning process of biological remains low . Could be also be caused by a lack of variation in the use of teacher learning model that students feel bored in participating in the learning process and students lack of understanding of the subject matter. This study aimed to examine the effect of the application of cooperative learning model two stay two stray accompanied by LDS at 9 Champaign Junior High School eighth grade academic year 2012/2013. This type of research is experimental, with the entire population of class VIII SMP 9 Padang. Sampling was done by purposive sampling. The term of the tests used in the study is multiple choice. From the research shows that the average value of the experimental class higher than the ave rage value of the control class. In the experimental class average value of 75.81 while the control class had an average value of 61,57. From the analysis of the` data obtained while tcount 5,15, ttable=1,67 thus tcount > t table which means that the hypothesis is accepted at the 95% confidencelevel ( α = 0,05 ). It can be concluded that cooperative learning model two stay two stray can improve student learning outcomes Junior High School eighth grade 9 academic year Padang2012/2013 .